Development Failure Analysis Kungkuk Tourism Village (Case Study in Punten Village, Batu City) - Ira Indawati; Muhammad Kamil; Yana Safriyana Hijri (Universitas Muhammadiyah Gorontalo, 2021)
This study aims to analyze the failure of the development of the Kungkuk Village Tourism Village in Punten Village, Batu City. Developing the tourism paradigm in Indonesia has made Tourism Villages a Trend in tourism development. Villages are required to manage and build village potential. However, in the implementation process, it often encounters obstacles such as lack of optimality and even failure in development. Researchers seek to see the role of actors and collaboration to form collaborations between government, private, community, academic, and media (Penta Helix) in developing Tourism Villages. The research method used is a qualitative method with a case study approach. The results showed that the failure of the development of the Kungkuk Village Tourism Village was triggered by a lack of support from the village government, and no village regulation provided an umbrella for the development of the Tourism Village. The strong sectoral ego triggers a low level of collaboration between the government, the private sector, the community, academia, and the media to develop Tourism Villages.